TEAHING CHILDREN WITH AUTISM SPETRUM DISORDERS NOSE BLOWING (Isagoge - Journal of Humanities and Social Sciences, 2021)
The impairments that are present in children with autism spectrum disorders (ASD) may lead to deficits in the development of daily activities, such as personal care and personal hygiene skills that are essential for independence. We used shaping procedure to teach three children with ASD nose blowing skills and this is the first ever research addressing this procedure application in children with ASD. We divided the skill into five steps and we used modeling prompt. All three participants mastered the nose blowing skill in 17 or 21 sessions. The first participant had the most difficulty with steps three and five, because of the transition from exhaling through the mouth to forceful exhaling from the nose. Shaping procedure was proven to be a successful as a teaching tool with children with ASD. These results are significant because the participants will be able to use the acquired skill every day and it will prevent possible future health issues. We believe it is necessary that both special educators and parents or caregivers of children with ASD implement personal hygiene teaching procedures in school or home environments.
Keywords: Shaping; Autism spectrum disorders; Nose blowing; Hygiene